2019
DOI: 10.1038/s41419-019-2079-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microRNA-711 limits angiopoietin-1 and Akt changes, tissue damage, and motor dysfunction after contusive spinal cord injury in mice

Abstract: Spinal cord injury (SCI) causes neuronal cell death and vascular damage, which contribute to neurological dysfunction. Given that many biochemical changes contribute to such secondary injury, treatment approaches have increasingly focused on combined therapies or use of multi-functional drugs. MicroRNAs (miRs) are small (20–23 nucleotide), non-protein-coding RNAs and can negatively regulate target gene expression at the post-transcriptional level. As individual miRs can potentially modulate expression of multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…Proteins from both perilesional cortex and ipsilateral hippocampus were extracted by RIPA buffer containing protease inhibitors and phosphatase inhibitor, then quantified by BCA assay. Twenty micro gram of proteins were loaded onto 4-20% SDS-PAGE gels (Cat# 4561096, Bio-Rad; Hercules, CA) as previously described (Sabirzhanov et al, 2019). Proteins were transferred onto nitrocellulose membranes and then blocked for 1 hr in 5% milk in 1× PBS containing 0.05% Tween 20 (PBS-T) at room temperature.…”
Section: Western Blottingmentioning
confidence: 99%
“…Proteins from both perilesional cortex and ipsilateral hippocampus were extracted by RIPA buffer containing protease inhibitors and phosphatase inhibitor, then quantified by BCA assay. Twenty micro gram of proteins were loaded onto 4-20% SDS-PAGE gels (Cat# 4561096, Bio-Rad; Hercules, CA) as previously described (Sabirzhanov et al, 2019). Proteins were transferred onto nitrocellulose membranes and then blocked for 1 hr in 5% milk in 1× PBS containing 0.05% Tween 20 (PBS-T) at room temperature.…”
Section: Western Blottingmentioning
confidence: 99%
“…The loss of neurons and glial cells can be considered as one of the main causes of permanent functional dysfunction after SCI, in which various cell transplants need to be used to compensate the loss of neurons and glial cells, guide axonal growth, and treat the SCI (Sabirzhanov et al, 2019;Li et al, 2017). In the present study, high-purity BMSCs obtained in vitro were transplanted into the injured spinal cord after induction of neuron-like cells by edaravone.…”
Section: Discussionmentioning
confidence: 95%
“…Bone marrow mesenchymal stem cells (BMSCs) possess incomparable advantages over other stem cells (Flouzat-Lachaniette et al, 2016;Hernigon et al, 2015;Long et al, 2018). In animal studies, BMSCs have displayed many advantages in the treatment of SCI (Ramalho et al, 2018;Sabirzhanov et al, 2019;Wang et al, 2019). Therefore, exploration of BMSC transplantation for SCI associates with clinical significance and broad research prospects.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Feng et al demonstrated that miR-204 was downregulated in the serum from SCI patients, and miR-204 overexpression promoted SCI recovery through inhibiting inflammatory response in SCI mice ( Feng et al, 2019 ). Boris Sabirzhanov et al showed that inhibition of miR-711 limited tissue damage and motor dysfunction after contusive SCI in mice ( Sabirzhanov et al, 2019 ). Wan et al revealed that miR-129-5p alleviated spinal cord injury in mice via suppressing the apoptosis and inflammatory response through HMGB1/TLR4/NF-kappaB pathway ( Wan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%